What is the long term acid inhibitor treatment in gastroesophageal reflux disease? What are the potential problems related to long term acid inhibitor treatment in gastroesophageal reflux disease? How should these cases be followed? - Hatemi, İbrahim; Esatoğlu, Sinem Nihal (Turkish Journal of Gastroenterology, 2017)
Abstract The meta-analyses of observational studies (OBS) showed the risk of any fracture and hip fracture slightly increased with proton pump inhibitor (PPI) treatment depending on the dose and regardless of time. This was not observed with histamine-2 receptor antagonists (H2RA). The risk of bacterial overgrowth and spontaneous bacterial peritonitis were increased with PPI therapy, but not with H2RA. In meta-analyses of OBS, a slight increase was observed in the risk of community-acquired pneumonia (CAP) in the early stages (<1 month) of PPI use and particularly at high doses. In a five-year LOTUS study, no difference was found in vitamin B12, folic acid, vitamin D, and calcium values in terms of the initial and end of follow-up levels. No increase in the risk of premalignant gastric lesions was observed in the meta-analysis of RCTs in which PPI treatment (≥6 months) was given to Helicobacter pylori negative patients. The risk of hypomagnesemia with PPI use was increased in patients having GFR<60, using diuretics, and over 65 years of age. Quasi-experimental studies showed a reduced zinc absorption with PPI use. In the meta-analysis of OBS, long-term (>1 year) PPI use increased the risk of fundic polyps, but no risk was found in shorter use. The meta-analyses of RCTS showed no difference between PPI and surgery or placebo arms and between the arms of H2RA and placebo in terms of all side effects. No difference was found between the PPI and H2RA arms both in all and serious adverse effects. Cite this article as: Hatemi İ, Esatoğlu SN. What is the long term acid inhibitor treatment in gastroesophageal reflux disease? What are the potential problems related to long term acid inhibitor treatment in gastroesophageal reflux disease? How should these cases be followed? Turk J Gastroenterol 2017;28(Suppl 1); S57-S60 Full Text Turkish